Wadel’s Concept of ‘incorporation’: A Means of Improving Sustainable Work Inclusion? - Frøyland, Kjetil; Nordberg, Tanja Haraldsdottir (Nordic Journal of Working Life Studies, 2024)
Sustainable work inclusion for marginalized individuals poses a significant challenge worldwide, not just in Nordic countries. In this paper, we explore the potential of ‘incorporation’, a concept formulated by Norwegian sociologist Cato Wadel, to offer fresh insights. We assess its contribution by 1) using it as an analytical lens to examine 20 micro-level, workplace-oriented studies conducted on inclusive work life in Norway, and 2) discussing it in the context of international research on work inclusion, job retention, and return to work. Our findings emphasize the relevance of Wadel’s concept as a general theory from which work inclusion efforts for marginalized individuals could benefit. Wadel’s concept highlights the role of colleagues and workplaces as complementary resources for sustainability, and underscores the importance of facilitating continuous reassurances of relationships and the development of status over time. These insights are often overlooked in work inclusion endeavors.